Removal of Cd2+ by N-CNS/ZnO nanocomposite from wastewater and reuse of Cd2+-N-CNS/ZnO in blood fingerprint detection - Y.B. Nthwane; B.G. Fouda-Mbanga; M. Thwala; K. Pillay (Results in Chemistry, 2022)
In this study, an N-CNS/ZnO nanocomposite was used to adsorb the Cd2+ ion from an aqueous solution, and the spent Cd-loaded absorbent was reused in blood fingerprint detection. N-carbon nanosheets (N-CNS) were produced from potato peels and then coated with ZnO nanoparticles. XRD, TEM, SEM, and FTIR were used to examine the sample functionality and Surface morphology. The effect of pH, adsorbent dosage, temperature, and time was examined using ICP-OES. Removal efficiencies optimum conditions for the Cd2+ were pH 8 with 99.05 %, adsorbent dosage of 100 mg with 99,97 %, temperature (55) with 93,34 % and time (3 h) with 91,24 %. Additionally, the adsorption pseudo-second-order and Langmuir isotherm models were best fitted for Cd2+ ion removal. The maximum adsorption capacity of Cd2+ ions was 8.762 mg/g. Therefore, N-CNS/ZnO nanocomposite can remove Cd2+ ions in wastewater, and its potential for re-use in blood fingerprint detection helps eliminate secondary environmental pollution.